Dynamics of Land Use and Land Cover Change in the South Talihya Watershed North Kivu, Eastern Democratic Republic of Congo - Musubao Kapiri Moïse; Pierre Ozer; Mulondi Kayitoghera Gloire; Ahadi Mahamba Jonathan; Uzimati Djurua Isaac; Musongora Kambale Muyisa; Kahambu Matimbya Hintou; Muhindo Sahani Walere (CV. Literasi Indonesia, 2022)
The anthropization of forest ecosystems has become a major environmental problem with negative impacts on biodiversity around the world. Responding to such a problem requires monitoring land use. Thus, this study aims to analyze the Spatio-temporal dynamics of land use (LULC) to implement effective management strategies for forest ecosystems in the South Talihya watershed in eastern DR Congo. For this, a diachronic study of Landsat TM+ satellite images from 1987 and 2001 and Sentinel-2 from 2020 was used. The results revealed that natural formations have regressed in favor of croplands and fallow mosaics in the Talihya South watershed. The forests which occupied 183.68 km2 in 1987, decreased to 140.94 km2 in 2001 and 108.2 km2 in 2020. Bare lands and buildings represented 87.54 km2 in 2020 against 115.33 km2 in 2001 and 58 .63 km2 in 1987. The current state of land use indicates that Crop lands, fallows, and pastures occupy a high surface area compared to forests and bare lands and buildings. These Crop lands, fallows, and pastures occupied 317.88 km2 in 1987, 303.74 km2 in 2001, and 373.34 km2 in 2020. The observed changes result from overexploitation of resources characterized by the expansion of agricultural lands and tree logging. The annual deforestation rate calculated from forested areas of Talihya South watershed between dates t0 (1987) and t1 (2020) was 1.60%. In view of these results, participatory land use planning is a way to ensure sustainable management of the existing residual forests in this watershed.